The Modern Approaches to Teaching English Increasing Qualities of Higher Educational Establishment Students in the Context of Globalization - Borova, Tetiana (Pedagogical Discourse, 2013)
The article deals with the concept «knowledge management» as an effective methods of higher educational establishment students teaching English educational process organization in the context of globalization. The basic approaches to the interpretation of notions «knowledge», «information», «knowledge management» are generalized. «Knowledge management» methodologies for the higher school students are shown. The ways of teaching English increasing qualities of non-language specialities students in informative society are discussed.